Understanding the perceived benefits, barriers, and cues to action for lung cancer screening among Latinos: A qualitative study - Alaniz-Cantú, Edgar I.; Goodwin, Kalese; Smith, London; Acosta, Eliany; Chávez-Iñiguez, Arlette; Evans, Mary Jo; Gaitán, Marcela; Lei, Fang; Yousefi-Nooraie, Reza; Fiscella, Kevin A.; Rivera, M. Patricia; Cupertino, Ana Paula; et al. (Frontiers in Oncology, 2024)
Introduction Rates of lung cancer screening among Latinos remain low. The purpose of the study was to understand the perceived benefits, barriers, and cues to action for lung cancer screening among Latinos. Methods Participants (N=20) were recruited using community-based recruitment strategies. Eligibility criteria included: 1) self-identified as Hispanic/Latino, 2) spoke English and/or Spanish, and 3) met the USA Preventive Services Task Force eligibility criteria for lung cancer screening. Interviews were conducted in Spanish and English, audio recorded, and transcribed verbatim. Using the health belief model, a qualitative theoretical analysis was used to analyze the interviews. Results Participants’ mean age was 58.3 years old (SD=5.8), half of the participants were female, 55% had completed high school or lower educational level, and 55% reported speaking more Spanish than English. All participants were currently smoking. Fourteen participants (70%) were unaware of lung cancer screening, and eighteen (90%) did not know they were eligible for lung cancer screening. Regarding lung cancer screening, participants reported multiple perceived benefits (e.g., smoking cessation, early detection of lung cancer, increased survivorship) and barriers (e.g., fear of outcomes, cost, lung cancer screening not being recommended by their clinician). Lastly, multiple cues to actions for lung cancer screening were identified (e.g., family as a cue to action for getting screened). Conclusions Most Latinos who were eligible for lung cancer screening were unaware of it and, when informed, they reported multiple perceived benefits, barriers, and cues to action. These factors provide concrete operational strategies to address lung cancer screening among Latinos.